Evaluación constructivista para la mejora del rendimiento académico en Biología. Año lectivo 2021 – 2022 - Pereira Armijos, Juana Isabel (2022)
This research emphasizes the application of constructivist evaluation techniques in the teaching-learning process, which contribute the improve of academic performance and acquire a long learning skill in students. The aim was to optimize the academic performance of the students, through the application of constructivist evaluation techniques, which contribute to generate significant learning in the subject of Biology in the first year of the BGU. A qualitative methodology was used, because, through it, from diagnosis to intervention and evaluation of results, relevant characteristics were determined around the application of Constructivist evaluation techniques. On the other hand, the present study, according to the nature of the information, is a participatory action research, due to the fact that a problem was previously diagnosed and, in order to solve it, the intervention proposal was implemented which contributes the improvement of the learning results in the target students. Evaluation and research instruments were applied, which made it possible to demonstrate the increase in academic performance in the searched sample. The application of a cross-sectional investigation was necessary, since the intervention proposal was applied through micro curricular planning in a certain period of time. The gotten results in the development of the research show that the most efficient constructivist evaluation techniques in the learning process during the research were: questionnaire, exhibition and album; that were efficient to verify the achievement of the educational objectives and to verify that the students learning has been achieved. Keywords: teaching learning – feedback – evaluation techniques – learning evaluation